Sleep features and the risk of type 2 diabetes mellitus: a systematic review and meta-analysis - Hongyi Liu; Hui Zhu; Qinkang Lu; Wen Ye; Tao Huang; Yuqiong Li; Bingqi Li; Yingxin Wu; Penghao Wang; Tao Chen; Jin Xu; Lindan Ji (Annals of Medicine)
Objective This study aimed to assess the associations between multidimensional sleep features and type 2 diabetes mellitus (T2DM).Methods We conducted a systematic search across the PubMed, Embase, Web of Science, and Scopus databases for observational studies examining the association between nighttime sleep duration, nighttime sleep quality, sleep chronotype, and daytime napping with type 2 diabetes mellitus (T2DM), up to October 1, 2024. If I2 < 50%, a combined analysis was performed based on a fixed-effects model, and vice versa, using a random-effects model.Results Our analysis revealed that a nighttime sleep duration of less than 7 h (odds ratio [OR] = 1.18; 95% CI = 1.13, 1.23) or more than 8 h (OR = 1.13; 95% CI = 1.09, 1.18) significantly increased the risk of T2DM. Additionally, poor sleep quality (OR = 1.50; 95% CI = 1.30, 1.72) and evening chronotype (OR = 1.59; 95% CI = 1.18, 2.13) were associated with a notably greater risk of developing T2DM. Daytime napping lasting more than 30 min augments the risk of T2DM by 7-20%. Interactively, the incidence of T2DM was most significantly elevated among individuals with poor sleep quality and nighttime sleep duration of more than 8 h (OR = 2.15; 95% CI = 1.19, 3.91).Conclusions A U-shaped relationship was observed between sleep duration and type 2 diabetes mellitus (T2DM), with the lowest risk occurring at a sleep duration of 7 to 8 h. Additionally, poor sleep quality, evening chronotypes, and daytime napping exceeding 30 min emerged as potential risk factors for T2DM. These high-risk sleep characteristics interacted with one another, amplifying the overall risk of developing the disease.